NOAC Adherence of Patients with Atrial Fibrillation in the Real World: Dosing Frequency Matters? - Hwang, Jongmin; Han, Seongwook; Bae, Han-Joon; Jun, Seung-Woon; Choi, Sang-Woong; Lee, Cheol-Hyun; Kim, In-Cheol; Cho, Yun-Kyeong; Park, Hyoung-Seob; Yoon, Hyuck-Jun; Kim, Hyungseop; Nam, Chang-Wook; Hur, Seung-Ho; Lee, Sang-Hoon (Thrombosis and Haemostasis, 2020)
Background and Objectives Nonvitamin K antagonist oral anticoagulants (NOACs) require stricter medication adherence. We investigated the NOACs adherence in real-world practice.Methods We screened all patients in our cardiology department the day before their outpatient appointment, over a 5-month period. We enrolled 719 consecutive patients who were taking NOACs for atrial fibrillation. The patients were contacted by phone or text to bring the remnant pills with them without any information why. Adherence was measured by the percentage of prescribed doses taken (PDT) (number of doses taken/number of doses expected to be taken from the last prescription × 100 [%]) and the Morisky Medication Adherence Scale (MMAS)-8.Results All 4 NOACs (apixaban 47.8%, dabigatran 21.2%, rivaroxaban 18.4%, and edoxaban 12.6%) were prescribed. The mean duration that the patients had been taking NOACs was 7.2 ± 5.7 months. The PDT was 95.4 ± 9.1% in the once-daily dosing group and 93.4 ± 12.7% in the twice-daily group, and the difference was statistically significant (p = 0.017). The mean MMAS was 2.6 ± 0.8. The proportion of patients with a PDT < 80% was 7.8%. They had a significantly higher MMAS than the PDT ≥ 80% group (3.4 vs. 2.5; p = 0.000).Conclusion Most patients who were taking NOACs had excellent adherence regardless of the dosing frequency. An MMAS ≥ 3 could be used as a simple screening tool for a poor NOAC adherence.
Keywords: medication adherence; anticoagulant; atrial fibrillation